Analysis of Factors Affecting the Use of ChatGPT at Mikroskil University: A Study Based on the Extended UTAUT2 Model - Sinaga, Joy Nasten; Panjaitan, Erwin Setiawan; Nurjanah, Sofinana (Brilliance: Research of Artificial Intelligence, 2024)
This study aims to identify factors that influence students' intention and behavior in using ChatGPT at Mikroskil University. The method used in this study is the Unified Theory of Acceptance and Use of Technology (UTAUT2), with the addition of the curiosity variable. Other variables analyzed included Performance Expectations, Effort Expectations, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit. To collect data, the research team conducted a survey of active students of the Faculty of Informatics at the university. Data analysis was conducted using Structural Equation Modeling (SEM), a method that allows researchers to understand complex relationships between variables. The results showed that several factors had a significant influence on the intention and behavior of using ChatGPT. Hedonic Motivation, Habit, and Curiosity were found to be the main factors driving the intention to use ChatGPT. Facilitating Conditions also contributed to the use of the technology. On the other hand, some variables did not show a significant impact on usage intention. Performance Expectancy, Effort Expectancy, Social Influence, and Price Value fall into this category. These findings suggest that the factors that drive technology use may vary, and highlight the importance of curiosity and personal motivation in the adoption of new technologies in higher education settings.